The Crisis and Regional Resilience in Europe: On the Importance of Urbanization and Specialization - Steven Brakman; Harry Garretsen; Charles van Marrewijk (Center for Economic Studies and ifo Institute (CESifo), 2014)
Using a rich data set on the EU regions, we analyze the relevance of two possible determinants of a region's resilience to shocks, the degree of urbanization and specialization. We take the Great Recession, the economic and financial crisis that started in 2008, as our shock and then analyze how the NUTS II EU regions differ in their resilience to the crisis in terms of unemployment and real GDP per capita. In prior research it has been well established that (EU) regions differ in their resilience to shocks but it typically remains unclear as to why regions differ in this respect. For the 2008- 2012 period, we find that the degree and nature of regional urbanization and specialization are important drivers of the resilience of EU regions. More in particular, we find that that EU regions with a relatively large share of its population in commuting areas in combination with a specialization in medium high tech industries are relatively resilient, that is were less affected by the crisis, a result that suggests a relationship with international trade.
Keywords: R11; R12; R15; 330; resilience; shock sensitivity; urbanization